Measuring DC Fields as Low as 0.5 nT by Using Bi-2223 Polycrystalline Superconductors - (:unkn) unknown (SPRINGER, 2013)
In this study a novel type of magnetometer capable of direct measurement of DC fields as low as 0.5 nT was described. The second harmonic voltage generated by polycrystalline superconductors inserted in AC and DC fields was used as sensor signal. The experiments have shown that a 0.5 nT DC field can be detectable by using Bi-2223 superconductors as the core material. The Bi-2223 reveals better sensitivity compared to the other high-T-c cuprates. Besides, the sensor works in a wide dynamical range (10(5) orders in magnitude), which increases its potential application areas.
Keywords: 2nd harmonic signal; High-T-c superconductor; DC-magnetometer; Ultra-low DC field measurements; Magnetic field sensor; GRAIN-BOUNDARIES; TEMPERATURE; SENSORS; SENSITIVITY; YBCO